1990
DOI: 10.1002/pola.1990.080281218
|View full text |Cite
|
Sign up to set email alerts
|

Rigid rod molecules as liquid crystal thermosets. I. Rigid rod amides

Abstract: A series of rigid rod amide monomers based on 2,2′‐disubstituted‐4,4′‐diaminobiphenyl were prepared and characterized by DSC and hot stage polarized light microscopy. The monomers were endcapped with maleimide, nadimide, and methylnadimide functionalities. With one exception, all of the materials could be thermally polymerized. Nematic liquid crystalline behavior was observed in three of the new materials which could be crosslinked in either the nematic or isotropic phase. Fast heating rates with hot stage pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 13 publications
0
58
0
1
Order By: Relevance
“…The IR spectra of polymers 7a-7d (Fig. 1) showed the complete disappearance of some characteristic absorption band peaks at 1785 and 895 (C-Cl) [17] and the appearance of some characteristic absorption bands at 1650, 1540 (amide), and 3320, 1540, 1325 cm-1 (secondary amine), etc. In addition, the IR spectra of Scheme 1. polymers 8a-8e (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectra of polymers 7a-7d (Fig. 1) showed the complete disappearance of some characteristic absorption band peaks at 1785 and 895 (C-Cl) [17] and the appearance of some characteristic absorption bands at 1650, 1540 (amide), and 3320, 1540, 1325 cm-1 (secondary amine), etc. In addition, the IR spectra of Scheme 1. polymers 8a-8e (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the commercially available Technochemie M-751 resin is based on the poly(amide-maleimide) resin concept [14]. A literature survey revealed that several bismaleimides containing amide linkages have been synthesized and polymerized recently [13][14][15][16][17], while poly[amino-(4-chloro)]maleimide with amide linkages has not been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The syntheses of the trimers and N-(4-hydroxyphenyl) multimode (HPMI) are essentially same as described previously [11][12][13] . The preparation of the blends of LCTs trimers was conducted using a cosolvent and precipitation.…”
Section: Synthesis: Lcts Trimers and Their Blendsmentioning
confidence: 99%
“…At present, numerous attempts have been made to study LCTs. Recently, many kinds of LCTs have been prepared by polymerizing monomers and oligomers with vinyl, 12 acrylate, 13, 14 methacrylate, 15, 16 ethynyl, 3, 9, 17, 18 epoxy, 19-21 nadimide, 22 and maleimide 23 functional groups to explore their application.It is well known that acrylate monomers easy form polymers by free radical polymerization, whereas allyl monomers polymerize hardly. Thus the use of acrylateallyl monomers, where both acrylate and allyl groups are combined in the same molecule, can firstly obtain soluble precursor polymers by free radical polymerization, then these linear precursor polymers can form LCTs by special polymerization at liquid crystalline state.…”
mentioning
confidence: 99%
“…At present, numerous attempts have been made to study LCTs. Recently, many kinds of LCTs have been prepared by polymerizing monomers and oligomers with vinyl, 12 acrylate, 13,14 methacrylate, 15,16 ethynyl, 3,9,17,18 epoxy, [19][20][21] nadimide, 22 and maleimide 23 functional groups to explore their application.…”
mentioning
confidence: 99%